Literature Review: Optimization Of Tablet Formula With Variations In Binder Type On The Physical Properties Of Tablets - Dias Firda Dias Firda; Nadam Adi Reksa; Auryn Difani Marfanie; Adelliana Putri Puspitasari; Mely Rosalinda (CV. AFDIFAL MAJU BERKAH, 2026)
Tablets are a widely used pharmaceutical dosage form due to their stability, dosage accuracy, ease of production, and ease of use. One important factor influencing tablet quality is the use of binders, which play a role in increasing interparticle cohesion and mechanical strength. This study aims to evaluate the effect of varying binder types and concentrations on the physical characteristics and performance of tablets, including hardness, friability, disintegration time, and dissolution profile. The method used was a literature review with a descriptive analytical approach based on scientific articles from indexed journals. The results of the study indicate that the type of binder significantly influences tablet properties. Synthetic binders such as polyvinylpyrrolidone (PVP) and Avicel tend to produce more consistent hardness and lower friability, while natural binders such as starch, gelatin, pectin, and mucilage show wider variation in results depending on the source and process. Increasing binder concentration generally increases hardness and decreases friability, but can prolong disintegration time and decrease dissolution rate. Therefore, optimal tablet formulation is achieved through a balance between mechanical strength and drug release capability, by using binders at optimum concentrations and considering interactions with other excipients and the manufacturing method.